Quinoline and Quinazoline Compounds as Antitubercular Agents - Desai, Pratibha; Naik, Bhadresh; Patel, Dinesh (Asian Journal of Chemistry, 2010)
Dimethyl quinolinyl and styryl-1,4-quinazolines as well as substituedsuch hydrazines have been prepared and tested for antitubercular activity.